Reading Igor Stravinsky’s Poetics of Music in Christian Higher Education - MacInnis, John (International journal of Christianity & education, 2022)
This article presents the composer Igor Stravinsky (1882–1971) as an historical educator in the context of the Charles Eliot Norton Lectures on Poetry at Harvard University (1939–1940), published as The Poetics of Music in the Form of Six Lessons. As music professors at North American institutions of Christian Higher Education, the authors each read Stravinsky’s Poetics with students in music classes. We describe here our different pedagogical methods and how we employ Stravinsky’s Poetics to form students with Christian approaches to culture-making.